2016
DOI: 10.1016/j.chiabu.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Entering out-of-home care during childhood: Cumulative incidence study in Canada and Australia

Abstract: Cumulative incidence provides a more accurate indicator than annual incidence rates of the number of children who experience out-of-home care during childhood. The study utilises a cohort of all children born in Western Australia (WA) 1994-2005 and Manitoba 1998-2008 using de-identified linked data. Life tables were used to calculate the age-specific cumulative incidence over time and for at-risk groups. Cox regression was used to compare risk factors for entry to care. Manitoba had a larger proportion of chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…Over the same period, the proportion of young children on CSOs who resided with their parent(s) at any point and at three years of age has decreased significantly. Similar trends of early removal from parents and increased use of out of home placements have been observed in some other countries (Gilbert, 2012), including England (McGrath-Lone et al, 2016Ubbesen et al, 2015), Australia and Canada (Marsh et al, 2017;O'Donnell et al, 2016). We found that at both time periods, most children who were removed from parental care had not been returned by the age of three years, and that the proportion who remained away from parents increased between cohorts.…”
Section: Discussionsupporting
confidence: 84%
“…Over the same period, the proportion of young children on CSOs who resided with their parent(s) at any point and at three years of age has decreased significantly. Similar trends of early removal from parents and increased use of out of home placements have been observed in some other countries (Gilbert, 2012), including England (McGrath-Lone et al, 2016Ubbesen et al, 2015), Australia and Canada (Marsh et al, 2017;O'Donnell et al, 2016). We found that at both time periods, most children who were removed from parental care had not been returned by the age of three years, and that the proportion who remained away from parents increased between cohorts.…”
Section: Discussionsupporting
confidence: 84%
“…A maternal socioeconomic risk profile was evident for infants in the “Problems Related to Social Environment/Upbringing” sample, as previously reported for out‐of‐home care . This pattern was, however, less pronounced for infants associated with SBS/AHT criteria, who, surprisingly, had parents who scored better for education, living together, and smoking.…”
Section: Discussionsupporting
confidence: 68%
“…The overall incidence of all infants with first entry into out‐of‐home care, although increasing during the study period, was comparable with that in Western Australia 1994 to 2005, slightly lower than that in England 1995 to 2008, and higher than that in Denmark, where the incidence has been declining …”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…The apology remains deficient when we closely look at social work intervention and public policy in the area of removal of Indigenous children. For instance a most recent study from Western Australia has revealed that Indigenous children were 'eight times' more likely to enter out-of-home care than non-Indigenous children (O'Donnell et al, 2016). In addition, Australia has highlighted Indigenous over-representation in the National Child Protection Framework, 2009-2020 with a view to reduce child protection intervention.…”
Section: Acknowledging Social Work As a White Profession In Australiamentioning
confidence: 99%